Analiza mikrobiologiczna osadu surowego i po kompostowaniu = The microbiological analysis of a raw sewege sludge and after composting process - Thi Bich Lock, Nguyen; Obertyńska, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The project shows the analysis of a secondery dehydrated sludge and after its compost with sawdusts, straw and lime. The sediment has been received from the sewage treatment plant in Łężyca (close to Zielona Góra) on the 23. l0.2000 year. The composts with secondary dehydrated sludge and dry mass 25% have been made accrding to following scheme:
Keywords: kompostowanie; analiza